EBV based cancer prevention and therapy in nasopharyngeal carcinoma - Ya Cao (Nature Portfolio, 2017)
Abstract Epstein–Barr virus is an important cancer causing virus. Nasopharyngeal carcinoma is an infection-related cancer strongly driven by Epstein–Barr virus. In this cancer model, we identified the major host targets of latent membrane protein 1 which is a driving oncogene encoded by Epstein–Barr virus in latency infection. latent membrane protein 1 activates several oncogenic signaling axes causing multiple malignant phenotypes and therapeutic resistance. Also, Epstein–Barr virus up-regulates DNA methyltransferase 1 and mediates onco-epigenetic effects in the carcinogenesis. The collaborating pathways activated by latent membrane protein 1 constructs an oncogenic signaling network, which makes latent membrane protein 1 an important potential target for effective treatment or preventive intervention. In Epstein–Barr virus lytic phase, the plasma level of Epstein–Barr virus DNA is considered as a distinguishing marker for nasopharyngeal carcinoma in subjects from healthy high-risk populations and is also a novel prognostic marker in Epstein–Barr virus-positive nasopharyngeal carcinoma. Now the early detection and screening of the lytic proteins and Epstein–Barr virus DNA have been applied to clinical and high-risk population. The knowledge generated regarding Epstein–Barr virus can be used in Epstein–Barr virus based precision cancer prevention and therapy in the near future.